2007
DOI: 10.2340/16501977-0087
|View full text |Cite
|
Sign up to set email alerts
|

Robot-mediated upper limb physiotherapy for patients with spastic hemiparesis: A preliminary study

Abstract: Objective: to investigate the clinical usefulness of the rEharoB therapeutic System, which provides passive robot-mediated physiotherapy for patients with spastic hemiparesis. Design: Controlled, randomized, preliminary study. Patients and methods: thirty patients with hemiparesis as a consequence of upper motor neurone lesion were divided randomly into 2 groups: robotic and control. Subjects from both groups received 30 minutes of Bobath therapy sessions on 20 consecutive work days. members of the robotic gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 12 publications
0
79
2
Order By: Relevance
“…Six robotic instruments were used in these RCTs: REHAROB [28], T-WREX [29], ARM-Guide [30], MIME [31][32], NeReBot [33], and MIT-Manus [26][27][34][35][36][37]. Most of the studies (and most robots) focused on the restoration of proximal UL function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six robotic instruments were used in these RCTs: REHAROB [28], T-WREX [29], ARM-Guide [30], MIME [31][32], NeReBot [33], and MIT-Manus [26][27][34][35][36][37]. Most of the studies (and most robots) focused on the restoration of proximal UL function.…”
Section: Resultsmentioning
confidence: 99%
“…The PEDro scores ranged from 2 to 7. All studies were considered high quality except Fazekas et al [28], which had a PEDro score of 2; as a result of the low PEDro score and also because the statistical information for the "between group comparison" and "point estimates and variability" was not included, this study was excluded from further analysis. In two of the studies, some of the baseline values were not comparable between the groups.…”
Section: Methodsological Quality Assessmentmentioning
confidence: 99%
“…This finding is confirmed by the two acute-and subacute-phase studies that used robotic training in addition to conventional therapy or in comparison with placebo (one involving the MIT-Manus [33], the other the NeReBot [21]) and revealed that additional robotic treatment in the acute and subacute phases leads to comparatively higher improvements in ADLs [22]. Conversely, at least one study on additional robotic training in the chronic phase reported that gains in ADL measures were not greater in the robotic group with respect to controls [47].…”
mentioning
confidence: 99%
“…Furthermore previous literature advocates that robot-assisted rehabilitation in post-stroke individuals have advantages in terms of clinical and biomechanical measures to regain arm motor function in comparison with conventional treatment [10][11][12][13][14][15][16]. Indeed performing repetitive movements with the affected limb of the post-stroke patient obtain functional gain thereby an increase of motivation which helps to use arm further [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%